What types of capital flows help improve international risk sharing?. (April 2022) - Islamaj, Ergys; Kose, M. Ayhan
Abstract: Cross-border capital flows are expected to lead to increased international risk sharing by facilitating borrowing and lending in global financial markets. We examine risk sharing outcomes of various types of capital flows (foreign direct investment, portfolio equity, debt, remittance, and aid flows) in a large sample of emerging market and developing economies. Our results suggest that remittances and aid flows are associated with increased international risk sharing. Other types of capital flows are not consistently correlated with better risk sharing outcomes. These findings are robust to the use of different econometric specifications, country-specific characteristics, and other controls.